Role Of Brand Awerenes, Price and Product Innovation on Smartphone Purchasing Decisions In Sidoarjo : Peran Kesadaran Merek, Harga dan Inovasi Produk Terhadap Keputusan Pembelian Smartphone di Sidoarjo - Fitanto, Julian Harris Ega; Prapanca, Detak; Sari, Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2023)
This descriptive research employs quantitative methods to investigate the intricate interplay between brand awareness, price, and product innovation in shaping smartphone purchasing decisions among 96 respondents in Sidoarjo. Employing a non-probability sampling technique with purposive sampling, the study utilizes multiple linear regression analysis through SPSS version 26 for data analysis. The findings underscore the pivotal roles of brand awareness, price, and product innovation in influencing smartphone purchase decisions in the studied region. This research contributes valuable insights into consumer behavior, offering implications for marketers and policymakers alike in understanding and leveraging these determinants to enhance the appeal and competitiveness of smartphone products. Highlights: Consumer Influence: The study reveals the significant impact of brand awareness, price, and product innovation on consumer decision-making processes when purchasing smartphones in the Sidoarjo region. Quantitative Analysis: Employing multiple linear regression analysis using SPSS version 26, the research provides a rigorous quantitative examination of the relationships between brand awareness, price, and product innovation in the smartphone market. Strategic Implications: The findings offer practical insights for marketers and policymakers, emphasizing the need to strategically manage brand awareness, pricing strategies, and product innovation to enhance the appeal and competitiveness of smartphone products in the targeted market. Keywords: Brand Awareness, Price, Product Innovation, Purchase Decision